Optimalisasi Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Pegawai Melalui Motivasi Kerja - Nugroho, Dewangga Adi; Sutianingsih, Sutianingsih (Public Policy, 2023)
This study examines how leadership, work discipline, and work motivation affect employee performance, with work motivation as the mediator. This study involved 30 Cepogo sub-district office employees from Boyolali Regency. This research is quantitative. Data analysis with multiple regression. The coefficient of determination of 80.8% indicates that the independent variable explains most of the employee performance variables. There were 19.2% of variables that did not affect employee performance. The findings of this study show a strong relationship between leadership and work discipline with employee performance. There is a positive but not statistically significant effect on employee performance caused by leadership. The results of the indirect influence of leadership variables can be influenced by work motivation variables on employee performance variables. Work discipline cannot be influenced by work motivation because the results of such variables are too small to be influenced by motivation. This is because the results of direct influence are greater than the results of indirect influence.